ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA SMP PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL - Sarah Isnaeni; Aditia Ansori; Padillah Akbar; Martin Bernard (Journal on Education, 2019)
This research is a qualitative descriptive study which aims to analyze the level of students' ability to solve problems in the material of One Variable Linear Equations and Inequalities with the categorization of the level of mathematical ability of high, medium and low connections. The research subjects were class VII students as many as 39 people. The form of data collection is giving 5 items written test questions. Based on the results of the analysis, the average value of the whole instrument questions mathematical connection ability obtained 71% for indicator 1, namely using relationships between mathematical topics, 92% for indicator 2, namely using mathematics in other subjects, 85% and 80% for indicator 3 and 4 that is using mathematics in everyday life, and 58% for indicator 5, which is to understand representations equivalent to the same concept. So if totaled and averaged at 77%. Then the mathematical connection ability of class VII junior high school students is high.